(untitled) (Communications in Computational Physics, 2010)
The spin-3/2 Ising model on the simple cubic lattice with nearest-neighbour ferromagnetic bilinear interaction (J > 0) is simulated on a cellular automaton by using the cooling algorithm improved from the Creutz cellular automaton. The phase diagrams of the model are constructed in the (D/J, kT/J) and (K/J, kT/J) plane. Comparison of the results are made with those of other methods. The temperature dependence of the order parameters and associated fluctuations are calculated at various of the model parameters and the static critical exponents are estimated within the framework of the finite-size scaling. The results are compatible with the universal Ising critical behavior except for D/J =−3 and K/J =−2.3.